PENGARUH MOTIVASI DAN SELF EFFICACY TERHADAP MINAT MAHASISWA AKUNTANSI DALAM BERKARIR DI BIDANG PERPAJAKAN - Payu, Anita Achmad; Marlinah, Andi (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2024)
Study aims to examine the influence of motivation and self-efficacy on the interest of accounting students with a concentration in taxation to pursue a career in the field of taxation. population in this study is 445 students from 2020 to 2022 of the Faculty of Economics and Business, Muslim University of Indonesia, Makassar. In the selection of samples, the researcher used the slovin formula so that the number of samples in this study was 51 students. results of this study show that all independent variables, namely motivation and self-efficacy, have a significant positive effect on the dependent variable, namely the interest of accounting students in a career in taxation.